Development and testing of a tender coconut punch and splitter - ANITHA JOHN SHAMSUDEEN K. P; Er. Jippu Jacob (Guide) (Tavanur 1997 Department of Farm Power Machinery and Energy)
Development and testing of a tender coconut punch and splitter
Development and testing of a tender coconut punch and splitter